The Role of Watching Historical Drama on the Values of Affiliation and Justice: A Study on the Revival of Ertuğrul - Osama Kanaker; Zulkiple Abd Ghani; Iyad L. Y. Abusalah; Emran (Mohamad Ali) Abdalah Al Qudah; Bushra Abuhaq (UKM Press, 2024)
Indexed by WOS/Scopus/MyCite